Jesus > religion : why He is so much better than trying harder, doing more, and being good enough - Bethke, Jefferson (Nashville : Thomas Nelson, 2013)
Most people are Christians by default. Bethke highlights the difference between teeth gritting and grace, law and love, performance and peace, despair and hope. He begins with the unvarnished tale of his own plunge from the pinnacle of a works-based, fake-smile existence that sapped his strength and led him down a path of destructive behavior. Crying out for a life greater than the one for which he had settled, Bethke discovered the real Jesus, who beckoned him beyond the props of false religion.
Introduction: Why I hate religion but love Jesus -- Will the real Jesus please stand up? -- Why I still think Jesus hates religion (and you should too) -- Fundies, fakes, and other so-called Christians -- Religion makes enemies / Jesus makes friends -- With religion, there are good and bad people / With Jesus, there are only bad people in need of grace -- Religion is the means to get things from God / If we seek Jesus, we get God -- With religion, if you are suffering, God is punishing you / God already punished Jesus on your behalf, so suffering is His mercy -- Religion says, "God will love you if..." / Jesus says "God so loved..." -- Religion points to a dim future / Jesus points to a bright future -- Why Jesus loves the church (and you should too) -- Conclusion: Do you know Jesus?
Includes bibliographical references (pages 205-211).
Keywords: Christianity -- Essence, genius, nature; Apologetics; Jesus Christ -- Person and offices; Christian life